Risk Analysis: A generalized Hazop methodology state-of-the-art, applications, and perspective in the process industry - Miguel Angel de la O Herrera; Aderval Severino Luna; Antonio Carlos Augusto da Costa; Elezer Monte Blanco Lemes (Fundação Oswaldo Cruz (FIOCRUZ), 2018)
Introduction: The Hazard and Operability Study is considered a feasible tool to assess risks, where complex technologies, require new strategies to guarantee efficiency, safety, and quality of products. Objective: To perform a Hazop publications review, to establish the state of the art, current procedures and perspectives in the pharmaceutical industry. Method: Hazop methodology and improvements to satisfy actual needs were structured. Subsequently, its application and integration with other risk tools, and experts systems, were analyzed to define the current approach and future perspectives. Results: The review allowed the understanding where models, simulations and specialized software offered adequate support to assess risk in current complex processes. In addition, an efficient definition of causes and consequences depends of expert systems, where simulations acquire experience through the creation of databases, reducing the need of specific process knowledge, which is a typical limitation of the conventional Hazop methodology. Conclusions: A review of the Hazop stateof- the-art highlighted the importance to assess risks within the process industry. However, the use of new technologies designed to meet regulatory affairs to guarantee safety and quality principles would require the ongoing improvement of the Hazop methodology, restricting the dependence of specialists, and increasing the use of expert systems.